Madlipz dalam Pembelajaran Daring MahÄrah IstimÄâ€™: Implementasi dan Analisis Persepsi Siswa - Audina, Noor Amalina; Mubarak, Mahfuz Rizqi (Departemen Pendidikan Bahasa Arab, 2021)
This researcher aims to explore the listening skill’ online learning process using the Madlipz application and analyze the students’ perceptions of the learning process. This study used a descriptive qualitative approach with three data collection techniques, namely observation, interviews, and documentation. From this study, the researchers concluded three steps used by the teacher, namely (1) preparing and sharing online class links using Zoom Cloud Meeting media, (2) several core activities such as greeting, motivation, and explanation of listening skill ‘learning objectives’. In this step, it is also explained how the videos provided by the Madlipz application are presented as teaching materials for listening skill ‘learning, (3) evaluating learning outcomes. Researchers also found various kinds of students’ perceptions which were categorized as positive and negative perceptions.